Behavioral model of a basic trabecular-bone multi-cellular unit using cellular automaton - Fonseca Velasquez, Aldemar (Visión electrónica, 2014)
Bone remodeling is the biological process through which old bone tissue is transformed into new bone through the action of a basic unit of bone remodeling (BMU). This paper presents a computational model to determine the variation of cell population caused by the presence of micro-fractures within the BMU during the remodeling process, also determines the spatial evolution at particular points of the trabecular bone surface. The remodeling process presented is governed by a twodimensional cellular automaton that evolves according to a set of rules and states, based on biological processes that occur in bone remodeling. The simulation of the remodeling process, programmed in MATLAB® performed in time intervals of 0.3 seconds, in the model showed a ratio of 20 osteoclasts to 190 osteoblasts. On the other hand, an approximate resorption time of 34 days and 150 days for formation was obtained. Bone mass showed a maximum percentage loss of 19%.